Processing Beautiful Banana Nugets for Assembly Group - Syamsu Nujum (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
This service is carried out to increase the ability of partners to create home industry products, change in productivity insights for productive people in entrepreneurship, increase household income in supporting the family economy. From the results of monitoring and evaluation, it is concluded that (1). The IbM program is very beneficial for the taklim assembly group, because with the home industry making beautiful banana nugget products, it can help increase the income of mothers. (2) The ibM Program Team and the Taklim Assembly group partners who have been given guidance and practice in making products can take advantage of the regional potential in their plantations or around their environment so that they can open up job opportunities and increase family income.